Traditional Medicine in The Modern Era: Analysis of Health Behaviors of Student Migrants in Makassar City - Dandi Purnama; Ibrahim Arifin; Nurul Annisa Muzakkir; Sitti Nurfadilla (Citra Media Publishing, 2026)
The sustainability of traditional medicine practices amid the expansion of modern biomedical systems is an important issue in health sociology studies. Among migrant students in Makassar City, traditional medicine practices continue to be used, even though they live in an urban environment with broad access to formal medical services. This study aims to analyze how traditional medicine practices are constructed, interpreted, and reproduced in the lives of migrant students in the modern era. This study uses a qualitative approach, including in-depth interviews, observation, and documentation. The study's results yield four main findings. First, the role of the family is central in shaping the continuity of traditional medicine practices through socialization and habits ingrained since childhood. Second, students demonstrate practical rationality in choosing treatment by comparing the effectiveness, cost, and healing experiences of formal medical services and traditional medicine. Third, the subjective dimension of illness interpretation shows that some illnesses are understood within a non-biomedical framework that includes spiritual aspects and inner experiences. Fourth, the reproduction of traditional medicine traditions occurs through family relationships, social networks, and digital mediation, which enable these practices to remain alive in a modern urban context. These findings indicate that traditional medicine is not merely a residual practice but rather the result of social constructions continuously negotiated in the lives of migrant students.